Virtual classroom in support of preschool second language learning (Philology, 2020)
Virtual learning environments and the Internet lead not only to the enrichment of alternatives for foreign language learning but also require a reconsidering of pedagogy and methodology. This article discusses the application of virtual classrooms in early foreign language learning. The data from a study conducted with 18 preschool teachers of foreign language, who switched to fully remote work in a virtual classroom during the COVID-19 lockdown, are presented. The main findings reveal that the virtual classroom meets the age characteristics of preschool children to a great extent and has the potential to provide a favorable environment for online foreign language acquisition.
Keywords: virtual classroom; second language learning; preschool; ICT